Bioactive compounds in different cocoa (Theobroma cacao, L) cultivars during fermentation - Cruz,Jaqueline Fontes Moreau (2015)
One component that contribute to the flavor and aroma of chocolate are the polyphenols, which have received much attention due to their beneficial implications to human health. Besides bioactive action, polyphenols and methylxantines are responsible for astringency and bitterness in cocoa beans. Another important point is its drastic reduction during cocoa processing for chocolate production and the difference between cultivars. Thus, the present study aimed to evaluate the modifications in monomeric phenolic compounds and methylxanthines during fermentation of three cocoa cultivars grown in southern Bahia. Cocoa beans from three cultivars were fermented and sun dried and monomeric phenolic compounds and methylxantines were determinated. The results showed that each cultivar have different amounts of phenolic compounds and the behaviour of them is different during fermentation. The amount of methylxantines varied but there was not a pattern for methylxantines behavior during process. In addition a huge reduction in phenolic compounds could be observed after drying. Differently of phenolic compounds, methylxantines did not have great modification after sun drying. So, the differences observed in this study between cultivars, take to the conclusion that the compounds studied in those cocoa cultivars have different behavior during fermentation and drying, which consequently, give to these cultivars differences in sensory characteristics.